Behavior of Hybrid CRRP-Concrete-Steel Double Skin Tubular Column under Axial Load - Hanaa A. Ali; Wissam D. Salman (Diyala Journal of Engineering Sciences, 2020)
Hybrid double skin tubular members (DSTMs) are composite section of three material FRP tube outside, steel tube inside and concrete sandwiches in between. The current study investigated the behavior of fourteen circular DSTCs under axial load. Every specimen is average of a pair of samples, the key parameters are the layers of outer carbon FRP tube, the compressive strength of concrete and the types of columns include (DSTC) and concrete filled FRP tube (CFFT). The test results show that the concrete has effected constrained between two tubes, that’s leads to increases strength and ductility of column, the most effective parameters has the number of layers of outer FRP tube the stress-strain relationship shows high ductile behavior of under compression test and the CFFT is superior in ultimate load compared with DSTC.